The brightest star in the sky - Keyes, Marian (Viking, 2010)
Fate is on its way to the tenants of 66 Star Street, bringing with it love and tragedy, friendship and heartbreak, and the power to change lives ... One of them is falling in love; another is torn between two lovers. For some, secrets they want to stay buried will come to light and for others the unveiling of those secrets will have tragic consequences.